Zonguldak Maden Teknisyen Mektebi (1940 – 1949) - (:unkn) unknown (My University, 2021)
Zonguldak’ta madencilik öğretimi 1924’de Zonguldak Maden MühendisMektebi’nin açılmasıyla başlamıştır. Bu okulun 1931’de kapatılmasınınardından 1949 yılına kadar geçen süre içinde Maden Tetkik ve Arama Enstitüsü(MTA) tarafından orta derecede madencilik teknisyenleri yetiştirmek üzereokullar açılmıştır. Bunlardan biri de 1940’da açılan ve ortaokul mezunlarınıalan Zonguldak Maden Teknisyen Mektebi’dir. Bu okul 1949’da Milli EğitimBakanlığı’na devredilmiş ve kapatılarak yerine maden mühendisi yetiştirenZonguldak Maden Teknik Okulu açılmıştır. Bu makalede Zonguldak MadenTeknisyen Mektebi’nin kuruluşu, yapısı ve 1940 – 1949 dönemindekiçalışmaları ele alınmıştır.

The provision of mining education in Zonguldak began in 1924 with the_x000D_ opening of the Mining Engineering School. After this school closed in_x000D_ 1931, mid-level schools for training mining technicians were established_x000D_ by the Institute of Mineral Research and Exploration (MTA). The Zonguldak_x000D_ Mining Technician School opened in 1940 and admitted secondary-school_x000D_ graduates. In 1949, this school came under the auspices of the Ministry of_x000D_ National Education and was then closed and replaced by the Zonguldak_x000D_ Mining Technical School, which trained mining engineers. In this article, the_x000D_ establishment, structure and activities of the Zonguldak Mining Technician_x000D_ School during 1940–1949 are discussed.
Zonguldak Mining Technician School (1940 – 1949)